Claiming the Republic: A Semiotic Analysis of Ownership and Citizenship in Taufik Ismail’s Poetry - Reni Wati Br Sagala Sagala; Rosmawaty Harahap (Journal of Aceh Studies, 2026)
A Discussions of ownership, sovereignty, and citizenship have long occupied a central position in Indonesian literary discourse, particularly in poetry that engages with questions of national identity and political ethics. Taufik Ismail’s poem “We Are the Legal Owners of This Republic” exemplifies this tradition by foregrounding ownership as a collective claim and moral responsibility. However, existing studies tend to treat the poem thematically, paying limited attention to the semiotic processes through which ownership is constructed and to its relevance for regional contexts such as Aceh. This study aims to examine how the meaning of ownership is articulated in the poem and to explore its implications for understanding civic consciousness within the broader framework of Aceh Studies. Employing a qualitative research design, the study uses a semiotic approach grounded in Roland Barthes’ theory of signification. The analysis focuses on key linguistic signs, including collective pronouns, legal terminology, and symbolic expressions, and interprets their denotative and connotative meanings in relation to socio-political discourses. The findings show that ownership in the poem is constructed as a collective and ethical claim rather than a purely legal status, emphasizing responsibility, solidarity, and popular sovereignty. The poem also functions as an implicit critique of political authority by reaffirming the moral legitimacy of the people. These findings contribute to literary studies by demonstrating the value of semiotic analysis for uncovering ideological meanings in poetry and to Aceh Studies by illustrating how national literary texts can illuminate regional concerns related to citizenship, autonomy, and collective identity.